The ’urban mobility integrated basin’ and its policy-oriented identification - ARCIDBUGI, Franco (European Spatial Research and Policy, 1994)
This contribution reassumes and updates the concept and operationality of the 'urban mobility integrated basin' (UMIB) as an appropriate unit of reference and prerequisite of rationality for any process of territorial planning and transport planning. The concept and rationality of the UMIB presuppose in fact the adoption (and consequent research) of a 'policy-oriented demand', albeit limited - in this specific case - to 'urban' mobility.